Revitalization of Jatidhuwur Jombang Mask Dance as An Effort To Reintroduce Local Cultural Values - Yanuartuti, Setyo; Winarko, Joko (Harmonia: Journal of Arts Research and Education, 2019)
Millennial era is an era where this generation is generally characterized by increasing the use and familiarity of communication, media and digital technology. This era will bring even further gaps in the attitude of this generation from the values of Indonesian life. The value of this nation’s life has long been stored under the arts and culture. In the midst of the downfall of the traditional art life, like the Jatid masked dance, we need the strategy for the young generation to value the local culture for filtering the exposure of foreign culture. This becomes the ground of current Jombang society which directing their art revitalization to the present cultural forms. That becomes the reason behind this study to be conducted. The purpose of this study is to realize the Jatidhuwur mask dance as a medium to introduce Jombang local cultural values to the current generation. The method used for revitalization is dance reconstruction. Reconstruction was carried out with the stages of excavation, setting the structure, developing elements of motion and accompaniment, and packaging, and introducing it to young people in Jombang. Data analysis uses an interactive model in the stages of data collection, data reduction, data presentation and conclusions. The results show that in the Jatidhuwur Mask dance performance there are local cultural values such as religious values, discipline values, life values, and the value of struggle. These local cultural values are revitalized and visualized through art elements such as themes (stories), plot, performance structure, and accompaniment in the touch of new cultivation. The dance is presented in the form of a single dance and a short dance drama (fragmentary), with a touch of technology.